COMPARATIVE STUDY OF SPRAY-DRYING AND FREEZE-DRYING ON THE SOLUBLE COFFEE PROPERTIES - GHIRIŞAN (MICLĂUȘ), Adina; MICLĂUŞ, Vasile (Studia Universitatis Babeș-Bolyai Chemia, 2017)
The paper presents a comparative study of some physical properties, microstructure and antioxidant capacity of soluble coffee obtained at laboratory scale using spray-drying (SD) and freeze-drying (FD) as dehydration techniques. SEM was used for monitoring structures and size of the coffee powder. The results of SEM show the difference in the microstructure with the used drying technique. SD dried coffee has only spherical shape, narrow distribution, with the particle mean size of about 10 mm and smooth surface. The FD dried coffee has spherical shape with the size of about 40 mm and flaky structure, non-spherical shape, with the dimensions between 10 x 20 mm and 30 x 90 mm. EPR was used for the determination of coffee antioxidant capacity. SD coffee powder shows a higher antioxidant activity in comparison with FD dried coffee.